ComDA: A common software for nonlinear and Non-Gaussian Land Data Assimilation. (May 2020) - Liu, Feng; Wang, Liangxu; Li, Xin; Huang, Chunlin
Abstract: Common software for land data assimilation is urgently needed to implement a wide variety of assimilation applications; however, a fast, easy-to-use, and multidisciplinary application-oriented assimilation platform has not been achieved. Therefore, we developed Common software for Nonlinear and non-Gaussian Land Data Assimilation (ComDA). ComDA integrates multiple algorithms (including diverse Kalman and particle filters), models and observation operators (e.g., common land model (CoLM), Advanced Integral Equation Model (AIEM)), and provides general interfaces for additional operators. Using mixed-language programming and parallel computing technologies (Open Multi-Processing (OpenMP), Message Passing Interface (MPI) and Compute Unified Device Architecture (CUDA)), ComDA can assimilate various land surface variables and remote sensing observations. High-performance computing and synthetic tests and real-world tests indicate that ComDA achieves the standard of common land data assimilation software with parallel computation, multiple operators, and assimilation algorithms and is compatible with many models. ComDA can be applied for multidisciplinary data assimilation. Highlights: ComDA is developed to build a common platform for data assimilation applications Parallel, multidisciplinary and scalability capabilities ensure ComDA works well ComDA promotes studies on the applications of land data assimilation